Study of TiO2 in anatase form on selected properties of new aliphatic-aromatic imines with bent shape towards organic electronics. Issue 6 (3rd May 2018) - Rozycka, Anna; Iwan, Agnieszka; Filapek, Michal; Gorska, Natalia; Bogdanowicz, Krzysztof Artur; Dabczynski, Paweł; Rysz, Jakub; Pociecha, Damian; Hreniak, Agnieszka; Marzec, Monika
ABSTRACT: Two bent-shaped imines (9E)-N-(3-((E)-(4-hexadecylphenylimino)methyl)benzylidene)-4-hexadecylbenzenamine (SL1) and (10E)-N-(3-((E)-(4-(perfluorooctyl)phenylimino)methyl)benzylidene)-4-(perfluorooctyl)benzenamine (SL2) were prepared by condensation reaction in N, N -dimethylacetamide to study their thermal, structural and electrochemical properties, as well as their mixtures with titanium dioxide. Chemical structure, temperature and TiO2 influences on the phase transition temperatures, enthalpy, texture and molecular dynamics of both imines were investigated by differential scanning calorimetry, polarising optical microscopy and Fourier transform middle-infrared absorption spectroscopy during heating and cooling. Changes in the surface morphology of the imines and their mixtures with TiO2 were registered by atomic force microscopy. X-ray study showed the tendency to form lamellas in the case of SL2 as an effect of the presence of two terminal perfluorinated alkyl chains connected to a polar mobile aromatic core, which resulted in microsegregation. Additionally, TiO2 influences the energy gap and HOMO–LUMO levels of imines as was detected by cyclic voltammetry. Finally, devices with two types of architectures, such as ITO/TiO2 /SL1(or P3HT)/Au and ITO/TiO2 /SL1:P3HT/Au were constructed and investigated under irradiation intensity of 97.7 mW/cm 2 . GRAPHICAL ABSTRACT: